(untitled) (Global Journal of Management and Business Research, 2023)
This paper explores the integration of lean six sigma and AI technologies and how they can enhance each other s value The paper introduces AI technologies such as Big Data Analytics Data Mining and Machine Learning and explains how they can be applied within Lean Six Sigma frameworks The paper also proposes a synergetic framework that combines AI tools and Lean Six Sigma methodologies The paper is structured as follows Section 1 is the introduction Section 2 gives a brief overview of Lean Methodologies and their frameworks Section 3 and 4 describe AI technologies focusing on Big Data Analytics and Machine Learning ML Section 5 presents the synergetic framework that embeds AI tools into Lean Six Sigma LSS frameworks